Aggregate Stochastic Implications of the Life Cycle Hypothesis - Clarida, R. H. (Quarterly Journal of Economics, 1991)
This paper sets forth some key aggregate stochastic implications of the Modigliani-Brumberg [19801 life cycle hypothesis and explores the extent to which a properly aggregated life cycle model can help to explain the first and second moment properties of changes in per capita consumption. The principal finding of the paper, which to my knowledge is new, is that smooth per capita consumption in the presence of permanent shocks to per capital labor income is exactly the outcome one should expect from a properly aggregated life cycle model in which saving for retirement, as well as for consumption smoothing, is a motive for asset accumulation. I.